Eiseley’s Stygian Oracle - Beachly, William (Humanimalia, 2012)
Nature provides an oracle, often when and where we do not seek one. Childhood encounters with animals, as with people, can be formative. Loren Eiseley’s  encounters may have been set him on the path of the vagrant. Such seekers may be drawn to places and things others shun (like caves, or spiders). This act of exploring beneath the surface of things is rarely completed or satisfying. Rather, like an oracle that speaks in half-audible whispers, much is left for the seeking mind to fill in. The scientist may feel their quest is more rational in execution than the mythic wanderer, but the world of the mind can allow for shape-shifting realities wherein both quests become one. This fearless willingness to listen to the oracle, and go wherever it leads, is both exemplary of good science and the human quest. I consider here what could have been the formative experiences that compelled Loren Eiseley, as a watcher of things, to look beneath familiar surfaces.  (WRB)